The Revolution of Quantity Surveying Profession in Building Information Modelling (BIM) Era: The Malaysian Perspective - Tee, Yun Ying; Mustafa Kamal, Ernawati (International Journal of Sustainable Construction Engineering and Technology, 2021)
Building Information Modelling (BIM) has becoming the current trend in the construction industry where quantity surveying serves as important discipline. Undeniably, BIM adoption has brought many advantages due to automation of multidimensional model platform that helps Quantity Surveyors (QS) to reduce arithmetic errors and removes many tedious tasks in conventional approach such as tendering and the production of bills of quantities (BQ). BIM will soon replace the traditional measurement done by QS if the Standard Method of Measurements (SMM) could be integrated in BIM. As a result, it is concerning that unemployment of quantity surveyors might be an issue if there is no revolution or adaptation of quantity surveying practices with the blossoming of BIM implementation in Malaysia. Hence, this research is carried out to determine the new skills needed by a quantity surveyor in order to keep pace with the implementation of BIM in Malaysia. Qualitative research method is used in this study in which semi-structured interview was carried out with 20 experienced QS that applies BIM technology in their practices. Data abstracted from the transcript of interviews was then coded though NVivo 12 Pro and analyzed by using content analysis method. At the end of the study, the findings revealed that the QS must attain IT skills and BIM software knowledge to align with BIM drive. It is thus recommended that thorough provisions of integrating traditional methods of quantifying and costing building projects with cutting edge technologies must be included in BIM standard to ensure that BIM can be adopted at its best in the profession with increase performance.